The Impact of Streamer Performance on Impulsive Buying through Vicarious Experience and Affective Reaction : Moderating Role of Shopping Motivation in E-Commerce Live Streaming - Ramdani, Fadli Rahmat; Syam, Winda Fitria (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the influence of Streamer Performance on Impulsive Buying through Vicarious Experience and Affective Reaction within the context of e-commerce live streaming on the Shopee Live platform. Additionally, this research examines the moderating role of Shopping Motivation in strengthening the impact of Streamer Performance on Vicarious Experience and Affective Reaction. Using the Stimulus-Organism-Response (SOR) model, this study identifies Streamer Performance as a stimulus influencing consumers’ impulsive buying behavior through organism processes, specifically Vicarious Experience and Affective Reaction. Data was collected from 225 respondents, comprising Millennial and Gen Z consumers in Indonesia, and analyzed using Structural Equation Modeling (SEM). The results show that Streamer Performance has a positive and significant effect on Vicarious Experience and Affective Reaction, which subsequently enhance Impulsive Buying within e-commerce live streaming. Furthermore, Shopping Motivation serves as a moderator, strengthening the relationship between Streamer Performance and Vicarious Experience and Affective Reaction, particularly among Gen Z, who are more familiar with digital interactions. This study contributes to understanding the mechanisms of impulsive buying in e-commerce live streaming and offers practical insight for e-commerce platforms to enhance their marketing strategies through live streaming. Keywords: Streamer Performance, Vicarious Experience, Affective Reaction, Impulsive Buying, Shopping Motivation, Live Streaming.